2017
DOI: 10.1002/pds.4338
|View full text |Cite
|
Sign up to set email alerts
|

Trends in utilization of benzodiazepine and Z‐drugs in Israel

Abstract: Conventional BZDs and Z-drugs remained the treatment of choice for sleeping disorders in Israel during the study period. These results are, in certain cases, in contrast to current practice recommendations and guidelines and point at a need in better dissemination of these guidelines among prescribers in Israel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…In line with previous reports of increased trends in zolpidem use, 36,38,45 we found zolpidem to be the only hypnotic with increased use, long-term use, and high-dose use. Previous studies 45,46 suggest that the long-term use of zolpidem may be more commonly associated with high-dose use and dose escalation than the use of zopiclone.…”
Section: The Use Long-term Use and High-dose Use Of The Most Commsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous reports of increased trends in zolpidem use, 36,38,45 we found zolpidem to be the only hypnotic with increased use, long-term use, and high-dose use. Previous studies 45,46 suggest that the long-term use of zolpidem may be more commonly associated with high-dose use and dose escalation than the use of zopiclone.…”
Section: The Use Long-term Use and High-dose Use Of The Most Commsupporting
confidence: 92%
“…1 However, an overall declining trend in BZD use and long-term use as well as a high nationwide prevalence of long-term BZD use among the older persons was in line with the results from other countries. [1][2][3][6][7][8]11,36,37 In contrast to this, a recent analysis from Israel found a gradual increase in the overall and especially hypnotic BZD and Z-drug consumption, 38 and a recent French study found a decrease in the number of incident hypnotic users, but not among incident anxiolytic users. 39 Despite a great variation between 7 European countries in the age and gender adjusted prevalence of BZD use, 2 constant international elements in BZD use can be found 40 : the higher prevalence in women and the steadily increasing use with age.…”
Section: The Use Long-term Use and High-dose Use Of The Most Commmentioning
confidence: 91%
“… 28 , 29 , 30 Concerns have also been raised about the increasing use of benzodiazepine-related drugs, often called Z-drugs, specifically, zolpidem. 28 , 30 , 31 …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Diazepam, is a medication of the benzodiazepine family, commonly used to treat a range of conditions including anxiety, 9,10 alcohol withdrawal syndrome, 11 muscle spasms, 12,13 seizures 14,15 and trouble sleeping. 16 Diazepam is majorly metabolized in the liver and mean plasma concentrations increased in approximate proportion to dose. 9 Analytical methods based on LC-MS for determination of oxycodone alone or with its major metabolites in a variety of matrices like human plasma, [17][18][19][20][21][22][23][24][25] blood and urine, 26 water samples 27 and in rat plasma 28,29 have been reported.…”
Section: Introductionmentioning
confidence: 99%